2004
DOI: 10.1200/jco.2004.04.105
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab in the Treatment of Advanced Non-Small-Cell Lung Cancer: Is There a Role? Focus on Eastern Cooperative Oncology Group Study 2598

Abstract: Combination paclitaxel, carboplatin, and trastuzumab is feasible. Toxicity appears no worse than cytotoxic therapy alone. Overall survival is similar to historical data using carboplatin and paclitaxel alone. However, patients with 3+ HER-2/neu expression did well in contrast to historical data suggesting potential benefit for trastuzumab in this rare subset of NSCLC. Critical assessment of trastuzumab's role in advanced NSCLC will require phase III trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
105
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(110 citation statements)
references
References 16 publications
1
105
1
3
Order By: Relevance
“…Two phase II studies did not find any convincing effect of trastuzumab treatment. 18,19 The first study by Gatzemeier et al enrolled 103 patients with HER2-positive lung cancers of different histologic subtypes (non-small cell lung cancer). In all, 17% of 617 screened patients were found to be HER2 positive by immunohistochemistry (2 þ , 3þ ) and were subsequently randomized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two phase II studies did not find any convincing effect of trastuzumab treatment. 18,19 The first study by Gatzemeier et al enrolled 103 patients with HER2-positive lung cancers of different histologic subtypes (non-small cell lung cancer). In all, 17% of 617 screened patients were found to be HER2 positive by immunohistochemistry (2 þ , 3þ ) and were subsequently randomized.…”
Section: Discussionmentioning
confidence: 99%
“…9,17 Clinical trials evaluating trastuzumab therapy in lung cancer so far have included between 17 and 59% of tested patients based on immunohistochemistry. 18,19 Intratumoral heterogeneity of overexpression/ amplification is another potential cause for nonresponding HER2-positive cancers. Heterogeneous ERBB2 amplification is rare in breast 20 but seems to be frequent (450%) in bladder or colorectal cancer.…”
mentioning
confidence: 99%
“…26 The single erbB2 mutation we have found was the same as the one repeatedly found by Shigematsu et al 26 Because very few NSCLC patients have gene amplification of erbB2, trastuzumab in the treatment of NSCLC might have a limited role. 9 Lung cancers that coexpress both EGFR and erbB2 appear to have more virulent behavior. 27 In addition, EGFR-erbB2 heterodimers are associated with a stronger and more sustained proliferative signal than EGFR homodimers.…”
Section: Discussionmentioning
confidence: 99%
“…Trastuzumab was approved for breast cancer 8 and clinical trials for NSCLC is underway. 9,10 Recently, we have found that novel EGFR mutations' status at ATP binding pockets in Japanese NSCLC patients were correlated with the clinicopathologic features related to good response to gefitinib. 11 These EGFR mutations are predominantly found in Japanese lung cancer patients (about 25%) when compared to USA patients (about 8% [12][13][14] to 10% 15 ).…”
mentioning
confidence: 99%
“…In 2006, response to trastuzumab in a patient with human epidermal growth factor receptor 2-(HER2-) mutated lung cancer was reported [11]. This was exciting because the activity of trastuzmab in previous lung cancer trials had been only modest [12]. In 2013, a European cohort study provided further evidence to support HER2-targeted therapy in patients with HER2-mutated lung cancer [13].…”
mentioning
confidence: 83%